2017
DOI: 10.1093/mnras/stx2677
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing matter profiles of spherically compensated cosmic regions in ΛCDM cosmology

Abstract: The absence of a physically motivated model for large scale profiles of cosmic voids limits our ability to extract valuable cosmological information from their study. In this paper, we address this problem by introducing the spherically compensated cosmic regions, named CoSpheres. Such cosmic regions are identified around local extrema in the density field and admit a unique compensation radius R 1 where the internal spherical mass is exactly compensated. Their origin is studied by extending the standard peak … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In general, cosmic voids are approximately spherical structures that tend to become more spherical with time. This result is known as the 'bubble theorem' [37], also discussed in [31][32][33][34][38][39][40]. Leveraging spherical symmetry (or quasi-symmetry), void formation and evolution have also been examined in the context of general relativity, including the Lemaître-Tolman-Bondi (LTB) dust models [41][42][43][44] and the quasi-spherical Szekeres models [25][26][27]45].…”
Section: Introductionmentioning
confidence: 99%
“…In general, cosmic voids are approximately spherical structures that tend to become more spherical with time. This result is known as the 'bubble theorem' [37], also discussed in [31][32][33][34][38][39][40]. Leveraging spherical symmetry (or quasi-symmetry), void formation and evolution have also been examined in the context of general relativity, including the Lemaître-Tolman-Bondi (LTB) dust models [41][42][43][44] and the quasi-spherical Szekeres models [25][26][27]45].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have put forward various forms of "universal" density profiles [48,49] that fit observations and catalogues. However, given the fact that cosmic voids are approximately spherical structures that tend to become more spherical as they evolve (see [50] for the first proof of this fact known as the "bubble theorem" 1 and also [4][5][6][7][51][52][53] for further discussions and comparison with Nbody simulations), it is also feasible to study them by means of spherically symmetric, exact and numerical solutions of Einstein's equations. As examples of analytic and semianalytic general relativistic studies, there are many based on Lemaître-Tolman-Bondi (LTB) dust models [54][55][56][57], or the more general non-spherical (but quasi-spherical) Szekeres models [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…These approximations, as well as the spherical evolution (e.g. [29] [30]) have been investigated in the literature and recently the authors of [28] have found that both Zeldovitch and spherical evolution lead to a similar evolution of an initially spherical density perturbation, which is in very good agreement with N-body simulations in some special cases (e.g. voids that are compensated, ∆(R = R v ) > 0, where R v is the radius of a void).…”
mentioning
confidence: 99%
“…For instance using the well-known Zeldovitch approximation [27], which links the initial density profiles ∆(a ini ) to a later time ∆(a) assuming no shell-crossing and mass conservation (e.g. [28]). These approximations, as well as the spherical evolution (e.g.…”
mentioning
confidence: 99%